(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Background Local anesthesia (LA) is the most common form of anesthesia that is used in most dental procedures. It is almost unavoidable in many dental treatments. Lidocaine is usually used with epinephrine in a single cartridge. Epinephrine is added to lidocaine to reduce toxicity, prolong duration of anesthesia and control bleeding. A common belief in medicine, dentistry and even among the patients is that the use of epinephrine is contraindicated in cardiovascular patients as epinephrine suddenly raises the blood pressure (BP) and hearth rate (HR). Objective The aim of this research is to study the effects of Local Anaesthesia containing adrenaline (vasoconstrictor) on Blood pressure and pulse rate in hypertensive patients and to ascertain the safety of using Local Anaesthesia with adrenaline in such patients. Design A prospective cross sectional study to analyze the effects of Local Anaesthesia containing adrenaline (vasoconstrictor) on Blood pressure and pulse rate in hypertensive patients Duration October 2016 to December 2017. Setting Osmania General Hospital, Hyderabad. Participants The study was conducted on 200 patients who underwent dental extraction at Osmania General Hospital, Hyderabad. Methods Out of 200 patients, 100 patients were normotensive patients with systolic blood pressure of <120 mm of Hg and diastolic blood pressure of < 80 mm of Hg and remaining 100 patients were Hypertensive patients out of which 50 patients had Stage I Hypertension (SBP 140 – 159 mm of Hg & DBP 90 – 99 mm of Hg) and 50 patients had Stage II Hypertension (SBP >160 mm Hg & DBP >100 mm Hg). All patients were given Inferior Alveolar Nerve Block followed by Lingual & Long Buccal Nerve Blocks with 2% Lignocaine with 1:2, 00,000 Adrenaline. The Blood pressure and pulse rate were recorded 6 times. Results All patients showed a considerable increase in Systolic and Diastolic BP recorded at 2 minutes but gradually showed a reduction until 60 minutes post-operatively. The pulse rate also demonstrated a sudden increase followed by gradual reduction to preoperative level. Conclusion All patients demonstrated a considerable increase in blood pressure and pulse rate but not significantly which may be attributed to stress induced due to dental extraction.